Using Theoretical Domains Framework (TDF) to understand implementation of a pragmatic clinical trial in Public Dental Service in Norway - E. A.S. Hovden; Rasa Skudutyte-Rysstad (BMC, 2021)
Abstract Background Most dental research in Norway has traditionally been conducted by universities, and the involvement of clinicians in research projects has not been a common practice. The aim of the present study was to identify behavioral factors that influence effective implementation of a pragmatic clinical trial in the Public Dental Service (PDS) in Norway and to understand which of these factors result in higher patient recruitment. Methods Dentists, dental hygienists, and dental assistants at nine Public Dental Service clinics in three counties in Norway involved in an ongoing pragmatic clinical trial were asked to complete an electronically distributed questionnaire based on the Theoretical Domains Framework (TDF). Results Thirty-seven out of 69 dentists and dental hygienists (54 %) and seventeen out of 57 dental assistants (30 %) answered the questionnaire. "Knowledge" was the domain with the highest mean response, suggesting strong confidence in personal knowledge and practical skills among the clinicians. Together with "beliefs about consequences," "organizational resources," and "environmental context," "knowledge" was the one of five domains identified as important behavioral determinants in patient recruitment to clinical trials by dental professionals. Conclusions The findings suggest that TDF was useful to understand factors affecting implementation of clinical trials in PDS and that several factors such as clinical relevance of trial to be implemented, organizational resources, and communication with the research team require more attention when planning and implementing clinical trials in PDS.